KUALITAS DADIH SUSU KERBAU DENGAN LAMA PEMERAMAN YANG BERBEDA - Evi Daswati; Hidayati dan; , Elfawati (State Islamic University of Sultan Syarif Kasim Riau, 2009)
An experiment wasjconducted to determine quality of dadih from buffalo milk with different incubation time. They were randomly allocated into 4 treatments in a randomized block design with 3 replications. Treatments were: A = 12 hours B =24 hours C =36 hours and D =48 hours. The result of this research was showed that 48 hours the best of incubation time at temperature 450 C, which nutrient content of dadih was crude protein 9.96